Analisis Kemampuan Berpikir Kritis pada Materi Aljabar Ditinjau dari Tipe Kepribadian Siswa Kelas VIII - Atiqah, Ummu; Amrullah, Amrullah; Kertiyani, Ni Made Intan (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Abstract This research aims to describe the critical thinking abilities in algebra material as viewed from the personality types of eighth-grade students at SMPN 8 Mataram. This type of research uses a descriptive qualitative method. The instruments used include a personality type test, specifically the Big Five personality questionnaire, critical thinking ability tests, and interview guidelines. Data from ten subjects were chosen from a group of 68 students based on their respective personality types for in-depth interviews. The results of the research show that students with openness to experience and neuroticism personality traits have moderate critical thinking abilities. In this case, students are able to meet 2 or 3 indicators. Students with openness and neuroticism personality types tend to be dominant in the analysis and evaluation indicators, while they tend to score lower in the interpretation and inference indicators. Students with extraversion and agreeableness personality traits have moderate critical thinking abilities as well. In this case, students are able to meet 2 or 3 indicators. Students with extraversion and agreeableness types tend to be more dominant in the analysis, evaluation, and inference indicators but tend to score lower in the interpretation indicator. Furthermore, students with conscientiousness personality traits have high critical thinking abilities. In this case, students are able to meet 3 or 4 indicators. Students with conscientiousness tend to be dominant in the interpretation, analysis, and evaluation indicators, while they tend to score lower in the inference indicator. Abstrak Penelitian ini bertujuan untuk mendeskripsikan kemampuan berpikir kritis pada materi aljabar ditinjau dari tipe kepribadian siswa kelas VIII SMPN 8 Mataram. Jenis penelitian ini adalah menggunakan metode kualitatif deskriptif. Instrumen yang digunakan berupa tes tipe kepribadian yaitu angket kepribadian big five, tes kemampuan berpikir kritis, dan pedoman wawancara. Dipilih data 10 subjek dari anggota 68 siswa berdasarkan masing-masing tipe kepribadian untuk dilakukan wawancara mendalam. Hasil penelitian menunjukkan bahwa siswa berkepribadian openness to experience dan neuroticisme memiliki kemampuan berpikir kritis sedang. Dalam hal ini, siswa mampu memenuhi 2 atau 3 indikator. Siswa dengan tipe kepribadian openness dan neuroticisme cenderung dominan dalam indikator analisis dan evaluasi, serta siswa cenderung rendah dalam indikator interpretasi dan inferensi. Siswa berkepribadian extraversion dan agreeableness memiliki kemampuan berpikir kritis sedang. Dalam hal ini, siswa mampu memenuhi 2 atau 3 indikator. Siswa dengan tipe kepribadian extraversion dan agreeableness cenderung lebih dominan dalam indikator analisis, evaluasi, inferensi dan cenderung rendah dalam indikator interpretasi. Kemudian, siswa berkepribadian conscientiousness memiliki kemampuan berpikir kritis tinggi. Dalam hal ini, siswa mampu memenuhi 3 atau 4 indikator. Siswa dengan tipe kepribadian conscientiousness cenderung dominan dalam indikator interpretasi, analisis dan evaluasi, serta cenderung rendah dalam indikator inferensi.